Perancangan Sistem Informasi Akademik Pada Sma Tangerang 1 Berbasis Web Menggunakan Framework Laravel - Ahmad Sodrul Tamam; Sukisno Sukisno; Asri Nurhafsari (JURNAL ILMIAH FAKULTAS TEKNIK, 2023)
The use of web-based information systems has been widely used in various fields, especially in education. In the field of education, this system is referred to as an academic information system, which is a platform designed to facilitate the implementation of administrative tasks in the academic field in educational institutions online. However, currently there are still many educational institutions that still use the old or manual method. SMA Tangerang 1 currently has not optimized the use of information systems effectively and still relies on manual or conventional methods such as using Microsoft Excel and Microsoft Word to input and manage data. In this research, the design of a web-based academic information system is carried out with the aim of increasing efficiency and effectiveness in managing grade management data, subjects, teacher data, student data at SMA Tangerang 1. Designed using the Laravel framework with Model View Control(MVC) architecture. This research adopts the Extreme Programming method in developing the application, resulting in a web-based information system that can be utilized by SMA Tangerang 1. The results of system testing show good performance, in accordance with user expectations.